Rational well spacings for CO2 miscible flooding based on superposed relationships between connected sand bodies - JI Yingchun (Youqi dizhi yu caishoulu)
The superposition relationships between sand bodies in glutenite reservoirs located in steep slope zones are complex， and the reservoir properties and connectivity vary significantly among different facies zones， making it challenging to determine the rational well spacings for CO2 miscible flooding. The single connected sand body was identified based on the geological characteristics. A reservoir numerical simulation model considering the random distribution of connected sand bodies was established to reveal the development scale， superposition relationship， and distribution density characteristics of connected sand bodies in different facies zones. The relationship between injection-production correspondence ratio and well spacing density was studied in different facies zones， and a new model of the relationship between recovery and well spacing density was constructed in combination with the Shelkachev formula. Furthermore， the net income future value method was employed to optimize and establish a basic chart for rational well spacings for CO2 miscible flooding. A composite superposition coefficient of connected sand bodies was introduced to further address the impact of the complex superposition relationships between connected sand bodies in glutenite reservoirs. Based on a randomly selected geological model and the basic chart of rational well spacings， the correction coefficient of well spacing was calculated for different composite superposition coefficients： the ratio of rational well spacing to basic rational well spacing. The study shows that the correction coefficient of rational well spacings is in a quadratic relationship with the composite superposition coefficient. A correction chart of superposition relationships between connected sand bodies is established， and a rationale well spacing optimization method with different permeability and crude oil viscosity is proposed. Two well groups of CO2 miscible flooding pilots are designed in the study area. The injection-production well spacing ranges from 310 m to 400 m according to the differentiated superposition relationships between connected sand bodies in different facies zones. Two rounds of trial injection have been carried out successively， effectively delaying the decline of glutenite reservoirs in the early stage of development. The annual decline rate of adjacent blocks is over 30% in the initial stage， and the pilot well group achieves continuous stable production for more than 30 months. The well spacing designs in the pilots are rational， and effective displacement is established.